India as an emerging power - Ganguly, Sumit (Frank Cass, 2003)
These essays examine India's relations with key powers including the Russian Federation, China and the USA and with key adversaries in the global arena in the aftermath of the Cold War. One positive relationship is that of India's relations with Israel since 1992.